Influence of Firm Size, Leverage, and Audit Quality on Audit Delay in Indonesian Property and Real Estate Firms - Rusdiah Hasanuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Background: Audit delay represents a critical factor affecting the timeliness of financial reporting and information usefulness for decision-making. The property and real estate sector faces unique challenges in audit processes due to complex asset valuations, project accounting, and regulatory requirements, making audit delay a significant concern for stakeholders. Objective: This study aims to examine the effect of firm size, leverage, and audit quality on audit delay in property and real estate companies listed on the Indonesia Stock Exchange (IDX). Methods: This quantitative study employed multiple regression analysis using a sample of 65 property and real estate companies listed on IDX during 2020-2024, resulting in 325 firm-year observations. Audit delay was measured as the number of days between fiscal year-end and audit report date. Independent variables included firm size (natural logarithm of total assets), leverage (debt-to-equity ratio), and audit quality (Big 4 auditor dummy). Control variables encompassed profitability, company age, and audit opinion type. Results: The findings reveal that firm size has a significant negative effect on audit delay (β = -8.743, p < 0.01), indicating that larger companies experience shorter audit delays. Leverage shows a significant positive effect on audit delay (β = 4.562, p < 0.05), suggesting that higher leverage increases audit complexity and duration. Audit quality demonstrates a significant negative effect on audit delay (β = -12.385, p < 0.01), confirming that Big 4 auditors complete audits more efficiently. The model explains 68.4% of the variance in audit delay (R² = 0.684). Conclusion: Firm characteristics and audit quality significantly influence audit delay in the property and real estate sector. Companies should focus on maintaining optimal capital structure, engaging high-quality auditors, and leveraging size advantages to minimize audit delay and enhance financial reporting timeliness.